1999
DOI: 10.1080/08327823.1999.11688385
|View full text |Cite
|
Sign up to set email alerts
|

Thawing of Foods in a Microwave Oven: II. Effect of Load Geometry and Dielectric Properties

Abstract: Non-uniformity of temperatures in thawing of food and biological materials inside a microwave oven is affected by size, shape, and dielectric properties of the load (food). The objective of this study was to relate the time to thaw and the non-uniformity of heating to the shape, size, and the dielectric properties of the load. The details of the heat transfer analysis, experimental measurement of thermal and dielectric properties, and temperature measurements are described in a companion paper. Results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…In food processing, multimode microwave experiments were carried out to determine the effect of power levels, power cycling, load geometry, and dielectric properties of thawing of food in a microwave oven. 41,42 It was found that the microwave flux at the surface and its decay were affected by the changes in the power level whereas power cycling has the same effects as continuous power. 41 Thawing time was found to increase linearly with the volume and an effective increase in the thawing rate was observed with decrease in the load aspect ratio.…”
Section: Multimode Microwave Applicators and Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…In food processing, multimode microwave experiments were carried out to determine the effect of power levels, power cycling, load geometry, and dielectric properties of thawing of food in a microwave oven. 41,42 It was found that the microwave flux at the surface and its decay were affected by the changes in the power level whereas power cycling has the same effects as continuous power. 41 Thawing time was found to increase linearly with the volume and an effective increase in the thawing rate was observed with decrease in the load aspect ratio.…”
Section: Multimode Microwave Applicators and Applicationsmentioning
confidence: 96%
“…41 Thawing time was found to increase linearly with the volume and an effective increase in the thawing rate was observed with decrease in the load aspect ratio. 42 Similarly, microwave thawing of frozen layer (water layer and ice) and microwave drying of unsaturated porous material were carried out by using 2.45 GHz microwave oven and the results show that the increase in electric field intensity input led to an increase in heating rate as well as thawing and drying rate. 15,43 Ceramic and Polymer Applications.…”
Section: Multimode Microwave Applicators and Applicationsmentioning
confidence: 98%
“…Power absorption can vary significantly with aspect ratio, defined as surface area/volume (cm 2 /cm 3 ). Previous researches showed The significant increase in power absorption with aspect ratio is mainly due to surface heating of ham that has a small penetration depth and this trend may not be true for low loss material [5]- [7]. The magnitude of energy absorption in materials is obviously related to the power output of the magnetron.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, frozen portion of the food absorb considerably less MW energy than the thawed food portion, because dielectric properties of ice are much less than that of liquid water ( [Chamchong and Datta, 1999a]; [Chamchong and Datta, 1999b]). In microwave oven, electric field distribution is highly sensitive to changes in the dielectric and thermal properties of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have made assumptions to simplify the problem and reduce the computational time. For example, instead of modeling Maxwell's equation, several researchers simplified the problem by using Lambert's law, which calculates dissipated power by assuming that the energy decays in the food exponentially from the material surface to deep inside of the material ( [Campanone and Zaritzky, 2005]; [Chamchong and Datta, 1999a]; [Chamchong and Datta, 1999b]; [Chen et al, 1993], [Khraisheh et al, 1997]; [Zhou et al, 1995]). Lambert's law does not represent the true electromagnetic field distribution inside the MW oven cavity (Datta & Anantheswaran, 2001).…”
Section: Introductionmentioning
confidence: 99%